Efektivitas Program Pengobatan Gratis Menggunakan KTP di Puskesmas Wedomu Kabupaten Belu - Joseph I. R. C Nenot’ek; Anzu Anjani Manimabi; Yanuarius Andelets Taloim; Melki Tamonob; Aldi Imanuel Tualaka; Christina Chindy Tatuin; Dewanry Putra Nakmofa; Margaretha Ignatin Subani; Maria M. Lino; Ernestus Holivil (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the effectiveness of the Free Medical Treatment Program Using Identity Cards (KTP) at Wedomu Community Health Center, East Tasifeto District, Belu Regency. The research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The analysis was based on Richard M. Steers' (1985) effectiveness theory, which includes goal attainment, system approach, and strategic constituencies approach. The findings indicate that the program has been fairly effective in improving public access to healthcare services and reducing medical expenses. From the goal attainment perspective, the program has facilitated easier access to healthcare services for the community. From the system approach perspective, the program is supported by funding, healthcare personnel, and service facilities, although limitations in human resources and supporting infrastructure remain. From the strategic constituencies perspective, beneficiaries expressed a high level of satisfaction with the services received. Supporting factors include local government commitment, healthcare workers’ dedication, and strong public demand for affordable healthcare services. Meanwhile, the main obstacles include limited healthcare personnel, inadequate service facilities, and insufficient public understanding of program procedures. Therefore, strengthening human resources, improving healthcare facilities, and enhancing program socialization are necessary to ensure sustainable improvements in healthcare service effectiveness.